(untitled) (Journal of Geography and Environmental Management, 2018)
According to the results of the international experts one of the most important measures for the development of tourism is its scientific and methodological support. There are no scientific and methodological basis of the industry, and currently, there are centers for research and forecasting of development of national tourism, which are financed from the state budget in developed countries, such as Germany, UK In order to ensure quality training of tourist staff at higher education institutions consider ways of organizing the issues of updating the content of education in research. One of the most pressing problems is the tourism of local literacy and cognitive interest of workers in tourism. And place names is the source of studying the history of the region. The combination of names and principles of systematization of place names and features of the local landscape since the early geographical point of view will be studied, analyzed, analyzed, and used in the tourism industry and will contribute to the implementation of the plan of tourism development plans. Updated educational program, included in the educational process - the study of the ways in which the organizers of the tourism industry, including tour guides, travelers, instructors in tourism, the theory of sustainable development, experience and information sources. The article presents a comprehensive study of the development of tourist and recreational centers in the country and a complex system of components, consisting of several components. From this point of view, the development of the tourism industry is characterized by a landscape any areas, i.e. tourism opportunities: tourism campaigns (sports activity), travelling, excursions, fun and healthy cultural level, as well as health promotion. Overall, this is a planned, personalized tourist activities of the candidate, organized in accordance with a favorable adverse environmental conditions. During trips and hikes organized by the tourists themselves tourists, information about the names and data was one of the urgent problems.